POSSIBILITIES OF CONSTRUCTION OF GENDER EQUALITY IN THE FIELD - Isaura Isabel Conte; Noeli Valentina Weschenfelder (Editora da Universidade de Santa Cruz do Sul, 2013)
The construction of gender equality in the field, refers to a look at the history of rural women and how they put the story since, have long been heavily stereotyped, even more inferior when compared to the other. This study aims to show the possibilities of building gender equality, with through the contribution of feminism, from research conducted in the Movement of Rural Women. We made theoretical studies, documentary analysis and interviews with activists and leaders of the Movement. We believe that feminism is something quite recent in the case of meeting the guidelines of the peasant struggle, but has significantly contributed in the struggle for liberation of women. We also stress that the learning and the force exerted by collective motion, was and is crucial in the fight for greater equality between women and men in their class and patriarchal society.